2013
DOI: 10.1111/echo.12310
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Value of Three‐Dimensional Transesophageal Echocardiography over Two‐Dimensional Transesophageal Echocardiography in the Assessment of Lambl's Excrescences and Nodules of Arantius on the Aortic Valve

Abstract: In this retrospective study, we identified 7 cases where Lambl's excrescences were identified by two-dimensional transesophageal echocardiography (2DTEE) and also had live/real time three-dimensional transesophageal echocardiography (3DTEE) studies available for comparison. We subsequently assessed them for the presence of Lambl's excrescences (LE) and nodules of Arantius (NA) on the aortic valve. After their identification, we qualitatively and quantitatively organized our findings by number, cusp location, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…As presented by our laboratory in prior 3DTEE studies, this modality has been able to acquire larger measurements in width (elevational dimension) in addition to height and length, which has allowed for the cal- culation of larger areas and volumes for different types of cardiac masses. [21][22][23] An ASP can be missed by 2DTEE as it occurred in three of our 34 single ASP cases and in three of our five double ASP cases. This scenario is a direct consequence associated with the 2D modality because of its single slice technique.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…As presented by our laboratory in prior 3DTEE studies, this modality has been able to acquire larger measurements in width (elevational dimension) in addition to height and length, which has allowed for the cal- culation of larger areas and volumes for different types of cardiac masses. [21][22][23] An ASP can be missed by 2DTEE as it occurred in three of our 34 single ASP cases and in three of our five double ASP cases. This scenario is a direct consequence associated with the 2D modality because of its single slice technique.…”
Section: Discussionmentioning
confidence: 59%
“…It is a retrospective study that identified patients who had undergone 3DTEE with visualization of an ASP and concomitantly had a 2DTEE during that same clinical encounter. As presented by our laboratory in prior 3DTEE studies, this modality has been able to acquire larger measurements in width (elevational dimension) in addition to height and length, which has allowed for the calculation of larger areas and volumes for different types of cardiac masses . An ASP can be missed by 2DTEE as it occurred in three of our 34 single ASP cases and in three of our five double ASP cases.…”
Section: Discussionmentioning
confidence: 73%
“…The detection of LEx is of particular importance in a relatively large proportion (~25%) of young patients with presumed cryptogenic stroke/TIA [31) in whom TEE is recommended. The detection of LEx in these patients, which will increase further with the use of three-dimensional TEE [32], may lead to misclassification of a stroke/TIA as cardioembolic, underdiagnosis of the true etiology of stroke/TIA, and potentially to unnecessary antiplatelet or anticoagulant therapy or even valve surgery. Thus, detection of LEx in a patient with suspected cardioembolism should not be considered a de facto cause of cerebroembolism.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to 2D echocardiography, 3D imaging can provide more accurate diagnostic information regarding the site, size, shape, and number of cardiac masses Table 1 29,30 …”
Section: Aortic Massesmentioning
confidence: 99%